CO Adsorption on Modified Mg–Al-Layered Double Hydroxides - T.C.M. Dantas; V.J. Fernandes Junior; A.P.B. dos Santos; F.A. Bezerra; A.S. Araujo; A.P.M. Alves (Adsorption Science & Technology)
Because of increases in the burning of fossil fuels, there is an increased emission of pollutant gases (e.g. CO 2 ) into the atmosphere. An alternative to minimize these emissions is to capture these gases using porous materials, such as layered double hydroxides (LDHs). In this study, LDHs were synthesized by co-precipitation of ion salts of Mg 2+ and Al 3+ . After the synthesis, the materials were treated with a template to expand the layers. The samples were then characterized by X-ray diffraction, thermogravimetric analysis/derivative thermogravimetry, adsorption/desorption of nitrogen, scanning electron microscopy/energy-dispersive X-ray spectroscopy and transmission electron microscopy. A CO 2 adsorption study was then performed to determine the adsorption capacity of the material in accordance with the contact time between the gas and the adsorbent. The adsorption capacities of LDHs and LDHs-P123 for CO 2 were 0.72 and 1.36 mmol/g, respectively, showing satisfactory results post-treatment.